Ritualising the Secular? Inter‐Religious Meetings in the 'Immanent Frame'. (15th February 2017) - Cheetham, David
Abstract : I take a philosophical approach and seek to address the question of inter‐religious rituals and practices with reference to what Charles Taylor has called 'the immanent frame.' Whilst considering the dynamics of inter‐religious or cross‐religious ritual, this article will focus mainly on the idea of rituality occurring in an immanent frame or habitus (Pierre Bourdieu). I will argue that whilst there are specific cultic rituals that need to be negotiated as part of any form of explicit inter‐rituality, there is a larger potential that is suggested by a broader anthropological vision. Moreover, an 'immanent turn' by religions may be the positive step towards the joint creation of meaning and practice in the public sphere.